Sistema de (in)justiça criminal e "IDS" liquidadas: LGBTQIA+ em prisões pernambucanas. - Morais, Neon Bruno Doering (2023)
In this study I sought to understand, from a multi-situated ethnographic fieldwork, the forms of management of the dissident bodies of gender and sexuality within male penitentiaries and to what extent the documents, especially the procedural records, (re)produce the logic of the Criminal Justice System, different from that experienced within the prison spaces. Therefore, the main objective is to analyze how LGBTQIA+ lives are managed in men's prisons, an environment that is both constricting and agency. The field of narrative research took place in four prison units, and, considering that the prison is a space of confinement that manufactures relationships, I sought to access in the interviews and conversations with the imprisoned people narratives about what crossed their lives and participated in their conflicts, also to understand how the norms of gender and sexuality were triggered in the midst of the negotiation processes, dispute, framing, subjection and agency. For the field of documentary research, I analyzed various types of documents about the incarceration of LGBTQIA+ people, such as regulations, procedural records, minutes of hearings, ministerial inspection reports and reports of projects developed in prison units in the state of Pernambuco. The multi-situationality was due, in addition to the combination of various research techniques used for data access, to access to different instances and processes of state, different ethnographic contexts, with interlocutors also quite different from each other. The study revealed that LGBTQIA+ people have unique experiences in men's prisons and receive additional punishment. The truth is that prison was exactly what was missing to liquidate their identities once and for all, even if they sometimes reaffirmed them precariously and violently – liquidated "IDs". This "data" appeared in all the paths offered by the field of research. I believe that the present study represents an important step to confront the violent and heteronormative logic produced by the system of criminal (in)justice on dissident bodies. To this end, critical criminology, high in its queer direction, has installed an innovative field of reflection to think about and complexify the processes of criminalization, victimization and prison conditions.